1987
DOI: 10.1002/jcb.240350207
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to the phosphomannosyl receptor inhibits recycling of receptor in fibroblasts

Abstract: The 215-kd phosphomannosyl receptor is involved in the transport of newly synthesized acid hydrolases to lysosomes and also mediates the pinocytosis of lysosomal enzymes by fibroblasts in culture. Recycling of receptors to the sorting sites is an integral part of both these processes. In this report, we describe the inhibition in human fibroblasts of both functions of the phosphomannosyl receptor by a rabbit antiserum to the bovine liver receptor. This inhibition cannot be completely accounted for by inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Previous studies (28) showed that exposure of human cells to antiserum to human CI-MPR inhibits enzyme endocytosis.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies (28) showed that exposure of human cells to antiserum to human CI-MPR inhibits enzyme endocytosis.…”
Section: Resultsmentioning
confidence: 97%
“…Fluorescein-conjugated transferrin (Tfn-FITC) was purchased from Molecular Probes (Eugene, OR). Goat antisera with specificity for the human CI-MPR was a kind gift from Dr W. Sly (Saint Louis University School of Medicine, St Louis, MO) 32 and was detected with an R-phycoerythrinconjugated donkey anti-goat IgG F(abЈ) 2 fragment from Jackson ImmunoResearch Laboratories (West Grove, PA). The grB-specific inhibitor was generously supplied by Dr N. A. Thornberry (Merck Research Laboratories, Rahway, NJ).…”
Section: Cell Lines and Reagentsmentioning
confidence: 99%
“…The IGF-IIR/MPR has been studied more extensively, and several lines of evidence suggest that it is the more important receptor for sorting acid hydrolases to lysosomes. (i) Antibody to the IGF-IIR/MPR blocked endocytosis and sorting (20)(21)(22). (ii) Mouse cells not expressing the IGF-IIR/MPR secreted most of their newly synthesized lysosomal enzymes (14,23,24).…”
mentioning
confidence: 99%
“…Sorting was inhibited only when both anti-HIGF-IIR/MPR antibody and anti-HSMPR antibody were added to the medium. This result suggested that sorting by the SMPR could only be demonstrated in the absence of the IGF-IIR/ MPR (22). We have transfected the HSMPR cDNA into mouse L cells that are defective for the IGF-IIR/MPR (23).…”
mentioning
confidence: 99%